(untitled) (Bangladesh Journal of Botany, 2025)
Comparative anatomical studies of Salvadora oleoides Decne. and Salvadora persica L. belonging to the family Salvadoraceae were performed for their better adaptations and survival. The results showed that hairs were only present on the outer surface of epidermis in S. oleoides Decne. due to its xerophytic conditions. In S. oleoides Decne. vascular bundles were arranged in circle while in S. persica, they were arranged in rays. In transverse section of stem, length and width of parenchyma were greater in S. oleoides Decne. while other tissues were greater in S. persica L. In T.S. of petiole, the length and width of metaxylem and protoxylem were greater in S. oleoides Decne. while other tissues were greater in S. oleoides Decne. In leaf epidermis, the length of epidermal cells was greater on the adaxial surface of S. persica L. These differences on the basis of anatomical characters and statistical analysis (correlation & Simple Regression Linear equations) can be helpful for their identification and classification of species. Bangladesh J. Bot. 54(1): 83-90, 2025 (March)